A case of ARF after chromopertubation with povidone iodine - Gautam, Savita S.; S. Gautam, Rajesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Povidone iodine is a widely-used antiseptic agent, especially for cutaneous lesions. Despite its apparent innocuousness, some cases of acute renal failure are reportedly due to iodine toxicity. Authors report a case of an acute renal failure secondary to povidone iodine exposure in a 22-year-old woman. She underwent a hysteroscopy for diagnosis of secondary sterility with bilateral tubal block in hysterosalpingogram, and povidone iodine was used as the contrast agent. She developed acute renal failure with oliguria, later on anuria during the postoperative period. Treatment with diuretics and hemodialysis led to a favourable outcome and return of normal kidney function. Mucosal administration of povidone iodine appears to lead to greater iodine toxicity than cutaneous administration. The clinical feature of this patient suggested tubular necrosis caused by iodine, after the other possible causes of acute renal failure were ruled out. Acute renal failure secondary to povidone iodine administration is possible, especially through mucosal surfaces. Outcome is favourable after the conclusion of exposure and symptomatic treatment.